Pengelolaan Dana Desa dalam Perspektif Teori Peran - Yahya Usman; Nilawaty Yusuf; Ayu Rakhma Wuryandini (STIE AMKOP, 2023)
This study aims to explore the extent to which the role of village officials in managing village funds is in accordance with TPK rules. This study used a descriptive qualitative methodology with data collection used were observation, interviews and documentation. This study also uses a data analysis model with an interactive model consisting of data reduction, information presentation and verification. The results of the study show the role of the Huangobutu village government in managing Village Funds based on a role theory perspective according to (Siagian, 2003) which consists of 5 main forms namely Stabilizers, Self-Executors, Pioneers, Modernizers, Innovators . in its application it is said to have